Investigation of the Interactions and Bonding between Carbon and Group VIII Metals at the Atomic Scale - Zoberbier, Thilo; Chamberlain, Thomas W.; Biskupek, Johannes; Suyetin, Mikhail; Majouga, Alexander G.; Besley, Elena; Kaiser, Ute; Khlobystov, Andrei N. (Wiley-VCH Verlag, 2016)
The nature and dynamics of bonding between Fe, Ru, Os, and single-walled carbon nanotubes (SWNTs) is studied by aberration-corrected high-resolution transmission electron microscopy (AC-HRTEM). The metals catalyze a wide variety of different transformations ranging from ejection of carbon atoms from the nanotube sidewall to the formation of hollow carbon shells or metal carbide within the SWNT, depending on the nature of the metal. The electron beam of AC-HRTEM serves the dual purpose of providing energy to the specimen and simultaneously enabling imaging of chemical transformations. Careful control of the electron beam parameters, energy, flux, and dose allowed direct comparison between the metals, demonstrating that their chemical reactions with SWNTs are determined by a balance between the cohesive energy of the metal particles and the strength of the metal–carbon σ- or π-bonds. The pathways of transformations of a given metal can be drastically changed by applying different electron energies (80, 40, or 20 keV), thus demonstrating AC-HRTEM as a new tool to direct and study chemical reactions. The understanding of interactions and bonding between SWNT and metals revealed by AC-HRTEM at the atomic level has important implications for nanotube-based electronic devices and catalysis.